High-NOON States with High Flux of Photons Using Coherent Beam Stimulated Noncollinear Parametric Down Conversion - Aziz Kolkiran (International Journal of Optics)
We show how to reach high fidelity NOON states with a high count rate inside optical interferometers. Previously, it has been shown that by mixing squeezed and coherent light at a beam splitter, it is possible to generate NOON states of arbitrary N with a fidelity as high as 94%. The scheme is based on higher-order interference between “quantum” down-converted light and “classical” coherent light. However, this requires optimizing the amplitude ratio of classical to quantum light, thereby limiting the overall count rate for the interferometric super-resolution signal. We propose using coherent beam stimulated noncollinear two-mode down-converted light as input to the interferometer. Our scheme is based on the stimulation of noncollinear parametric down conversion by coherent light sources. We get a better flexibility of choosing the amplitude ratio in generating NOON states. This enables super-resolution intensity exceeding the previous scheme by many orders of magnitude. Therefore, we hope to improve the magnitude of N-fold super-resolution in quantum interferometry for arbitrary N using bright light sources. We give improved results for N = 4 and 5.